EXPERIENTIAL MARKETING'S IMPACT ON CUSTOMER LOYALTY THROUGH SATISFACTION: GOJEK USERS IN SEMARANG - Rindang Nurtantio Swasono; Yohan Wismantoro (Universitas Dian Nuswantoro, 2026)
In the rapidly evolving ride-hailing industry, experiential marketing plays a crucial role in fostering customer satisfaction and loyalty, particularly amid intense competition among platforms like Gojek in urban areas such as Semarang, Indonesia. This study addresses gaps in prior research, which have often focused on the retail or fintech sectors, by examining the impact of experiential marketing on transportation services, where customer experiences directly influence retention and business sustainability. This research aims to investigate the relationship between experiential marketing and customer loyalty, mediated by customer satisfaction, among Gojek users in Semarang. A quantitative approach was employed, targeting Gojek users in Semarang. Data were collected from 100 respondents via purposive sampling and questionnaires. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for analysis, incorporating outer and inner model evaluations, hypothesis testing, and mediation effects. These findings highlight the mediating role of satisfaction in fostering loyalty through positive experiences, offering practical insights for ride-hailing companies to prioritize comprehensive customer engagement strategies.